Electro-spun nanofibers-based triboelectric nanogenerators in wearable electronics: status and perspectives - Deyin Tao; Ping Su; Aiping Chen; Dawei Gu; Mustafa Eginligil; Wei Huang (npj Flexible Electronics)
Abstract Electro-Spun nanofibers (ESNs), with their design flexibility, tailorable morphologies, and high surface area, are well-favored as triboelectric nanogenerator (TENG) materials for wearable electronics. Here, various aspects of ESNs-based wearable TENGs were examined. After introducing the most common TENG operating modes, an insightful overview of wearable TENG applications based on ESNs was presented. In this survey, a special attention is paid to wearable sensing, human-machine interaction, self-powered devices, and amplified energy harvesting. Efforts towards improving energy conversion efficiency, material durability, and compatibility with diverse wearable platforms were visited. Finally, a perspective based on particularly material aspect of ESNs is given, which could be insightful in tackling prevailing challenges and giving birth to new directions.